The influence of product quality and brand image on consumer loyalty is mediated by customer satisfaction - Alfeb, Nochia Vedora; Salim, Muhartini (Gema Wiralodra, 2024)
Based on BPS 2021, Indonesia's cosmetics industry grew by 9.61%. BPOM recorded a 20.6% surge in cosmetics companies in 2022 and continued to increase in 2023. Indonesians trust local products to care for themselves; for example, Scarlett whitening dominated the market share with 11.32% (thus becoming the top brand), with IDR 23.8 billion in the second quarter of 2022. The research I conducted in October 2023 was quantitative, distributing questionnaires filled out by 140 respondents who used Scarlett Whitening throughout Indonesia. Then, the data was processed using SmartPLS4 (PLS-SEM). The results showed that Product quality has a significant effect on customer satisfaction, Brand image has a significant effect on customer satisfaction, Product quality has a significant effect on Customer Loyalty, Brand image has a significant effect on customer loyalty, Product quality has a significant effect on customer loyalty through customer satisfaction as a mediating variable; Brand image has a significant effect on Customer Loyalty through customer satisfaction as a mediating variable; Customer satisfaction has a significant effect on Customer Loyalty. These results provide insight for consumers in choosing products and things for companies that can increase Customer Loyalty. It is recommended that future research consider more factors that affect customer loyalty.